Inventarisasi Varietas Tanaman Puring (Codiaeum variegatum (L.) Rumph. ex A. Juss.) di Desa Jeruju Besar Kecamatan Sungai Kakap Kabupaten Kubu Raya - Mas Akhbar Faturrahman; Azfa Fadhilah; Nufitasari Nufitasari; Inne Aqmarina Filza; Hayatul Fajri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Indonesia is a country that has high biodiversity. One of Indonesia's biodiversity plants is the croton plant (Codiaeum variegatum (L.) Rumph. ex A. Juss.). The Croton plant is one of the plants used by the general public as an ornamental plant because of the various shapes and colors of its leaves. This research aims to carry out an inventory of various varieties of croton plants in Jeruju Besar Village, Sungai Kakap District, Kubu Raya Regency, West Kalimantan Province. This research is a qualitative descriptive study with stages including taking samples of croton plants followed by identifying and providing descriptions of croton plants. The results of the research show that there are 24 varieties of croton based on the leaves color and shape, namely ‘Daylight’, ‘Mentimun’, ‘Gold Star’, ‘Burgundy’, ‘Bor Merah’, ‘Batik Mini’, ‘Mentega’, ‘Kecapi’, ‘Trisula’, ‘Tiger’, ‘Spaghetti Three-Color’, ‘Kura Lokal Variegata’, ‘Emping’, ‘Koi’, ‘Manik Maya’, ‘Jazzy Hybrid’, ‘Lele Kirmizi’, ‘Holland’, ‘Kura Batu’, ‘Jumbo Jet’, ‘Adreanum’, ‘Keris’, ‘Jet Amerika’, and ‘Kelabang’.